PANDANGAN HUKUM ISLAM TENTANG CALON SUAMI MEWAKILKAN AKAD QOBUL PERNIKAHAN KEPADA ORANG LAIN PADA MASA PANDEMI - Eko Setiawan; B Baehaqi; Agus Fatuh (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
Terms and pillars have a great influence on legal actions, especially those relating to the legitimacy of legal actions. In a marriage there must be conditions and pillars, meaning that the marriage is void if both are absent or incomplete. This research aims to examine the ability of prospective husbands to represent their marriage vows to other people during the covid-19 pandemic. This type of research is research with data collection techniques of observation, interviews, documentation and literature which is then analyzed by data reduction techniques, data display and drawing conclusions. The results of this study indicate that representing the marriage qabul can be done if the prospective husband is in an emergency, so he cannot pronounce his marriage qabul directly and has received approval from the prospective bride to represent her marriage qabul contract.